TEAM LEADERSHIP how to define, apply, and measure it. - Ribbens, Geoff; Abraham, Mark; Cumming, Alistair ([S.l.] : PRODUCTIVITY PRESS, 2024)
This work has developed the Leadership Pathway Audit(tm) that measures the effectiveness of leadership for any leader or any team and will, over time, chart how leadership changes as any factor of the leader, the team or the situation changes.
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- Foreword -- Preface -- Acknowledgements -- About the Authors -- 1. The Four Errors That Have Prevented Progress in Our Understanding of Leadership and the Importance of Team Member Perceptions -- 2. Emergent Team Leadership Discovered, Described, Explained, and Measured -- 3. Case Studies Based on Emergent Team Leadership and the Leadership Pathway Audit$1!" (B-- 4. Features, Benefits, and Practical Application of ETL and the LPA -- 5. The Building Blocks of Emergent Team Leadership Are Derived from Basic Social Science -- 6. How We Arrived at the 12 Key Forms of Influence Found in Emergent Team Leadership -- 7. How Other Researchers Have Approached the Concept of Leadership: Their Strengths and Weaknesses in Comparison to Emergent Team Leadership -- 8. Political Leaders: The Context of Discovery -- 9. Testimonials and Final Thoughts -- References -- Indexs
Keywords: Leadership